22 months follow-up of deep marginal acquisition with thermacut bur in management of deep subgingival interproximal carious lesions: a case report - Ahmed Khairy Elmorsy; Shereen Hafez Ibrahim; Hani Mohamed Essam El-Nahass; Ahmed El Zohairy (BMC Oral Health)
Abstract Background Minimally invasive dentistry is now becoming the forefront of restorative dentistry, involving less traumatic treatment protocols, conservation of tooth structure and surrounding tissues, enhancing the long-term survivability of treated teeth, and improving the overall quality of life for patients. Objective The current case report was conducted to evaluate acquiring deep subgingival interproximal carious lesions by the mean of thermacut bur gingivectomy, in terms of patient satisfaction through pain evaluation, Bleeding on Probing, Pocket Depth, Crestal Bone Level evaluation, and restoration evaluation using modified USPHS criteria. Material and methods A patient with a deep proximal cavity in the posterior tooth was thoroughly examined and underwent Thermacut Bur Gingivectomy (TBG) after caries removal followed by direct resin composite restoration of the prepared cavity. Patient Satisfaction using a Visual Analogue Scale (VAS) as a primary outcome. Bleeding on Probing (BoP), Probing Depth (PD), and Crestal Bone Level (CBL) as secondary outcomes, and Marginal Integrity using Modified USPHS Criteria as a tertiary outcome, were evaluated at the baseline, immediate post-operative, 6 month, 12 month and 22 month follow-up intervals. Results Thermacut bur gingivectomy revealed minimal immediate post-operative pain, minimal time-consuming procedure, minimal (BoP), appropriate (PD) and no need for extra specialty involvement in the treatment of deep interproximal carious lesions in addition to preservation of the alveolar bone crest with excellent restoration margin at different time intervals. Conclusions Thermacut bur gingivectomy can be considered a valid treatment for managing of deep subgingival interproximal carious lesions in vital teeth. Thermacut bur gingivectomy can be introduced as an easy technique for clinicians in the management of deep subgingival interproximal carious lesions, without the need to refer patients to periodontists and without the need for special devices.